A genetic score for the prediction of beta-thalassemia severity - Danjou, F.; Francavilla, M.; Anni, F.; Satta, S.; Demartis, F.-R.; Perseu, L.; Manca, M.; Sollaino, M. C.; Manunza, L.; Mereu, E.; Marceddu, G.; Pissard, S.; et al. (Haematologica (Roma), 2015)
Clinical and hematologic characteristics of beta(β)-thalassemia are determined by several factors resulting in a wide spectrum of severity. Phenotype modulators are: HBB mutations, HBA defects and fetal hemoglobin production modulators (HBG2:g.-158C>T polymorphism, HBS1L-MYB intergenic region and the BCL11A). We characterized 54 genetic variants at these five loci robustly associated with the amelioration of beta-thalassemia phenotype, to build a predictive score of severity using a representative cohort of 890 β-thalassemic patients. Using Cox proportional hazard analysis on a training set, we assessed the effect of these loci on the age at which patient started regular transfusions, built a Thalassemia Severity Score, and validated it on a testing set. Discriminatory power of the model was high (C-index=0.705; R(2)=0.343) and the validation conducted on the testing set confirmed its predictive accuracy with transfusion-free survival probability (P<0.001) and with transfusion dependency status (Area Under the Receiver Operating Characteristic Curve=0.774; P<0.001). Finally, an automatized on-line calculation of the score was made available at http://tss.unica.it. Besides the accurate assessment of genetic predictors effect, the present results could be helpful in the management of patients, both as a predictive score for screening and a standardized scale of severity to overcome the major-intermedia dichotomy and support clinical decisions.